(untitled) (Lex localis - Journal of Local Self-Government, 2020)
The article contains an analysis of the issue of public interest pursued by the municipal government in the field of nature conservation, demonstrated on the example of individual forms of nature conservation, the latter term being the concept used by environmental law scholars. Moreover, it covers natural monuments, documentation stands, ecological grounds and natural and landscape complexes, which are established through a resolution of the municipal council, which constitutes an act of local law. On the other hand, administrative prohibitions introduced for this purpose in an act of local law must have statutory authorisation and they should take into account the constitutional principle of sustainable development and the principle of proportionality. This is because these prohibitions restrict the right of ownership of immovable property situated in their area. Moreover, such an act of local law shall also be subject to the judicial review by an administrative court, having been challenged by the addressee of such act, provided that the addressee has also a legal interest, not only a factual interest.